INTRA-OCEANIC SUBDUCTION SYSTEMS: INTRODUCTION - Leat P.T.; Larter R.D. (My University, 2003)
Intra-oceanic arcs are the simplest type of subduction,systems in that they occur where overridding plates of subduction zones consist of oceanic rocks, contrasting with arcs built on continental margins. They comprise,some,40% of the subduction,margins,of the Earth. The better-known examples include the Izu-Bonin-Mariana arc, the Tonga- Kermadec arc, the Vanuatu arc, the Solomon arc, the New Britain arc, the western part of the Aleutian arc, the South Sandwich arc and the Lesser Antilles arc. They are thought to represent the first stage in the generation of continental crust from oceanic materials. They are generally more inaccessible than continental arcs, but, for a variety of reasons, provide insights into processes in subduction,zones that are impossible or difficult to glean from the better-studied continental arcs. Intra-oceanic arcs typically have a simpler crustal structure than arcs built on continental crust, although there are significant differences between examples. Geochemically, magmas erupted in intra-oceanic arcs are not contaminated